A corpus-based comparative study on the superlative forms in British English and Singapore Colloquial English. Issue 4 (2nd October 2017) - Gu, Qianping
Abstract : The study compares Singapore Colloquial English (SCE) and British English with respect to the usage of the two superlative forms, inflectional and periphrastic. I predicted that the periphrastic forms were more frequent in SCE than in British English since its substrate languages, Chinese and Malay, only have periphrastic forms. However, the results show that there is no statistical difference between the two varieties of English. I further carried out a close look at the superlative forms for the disyllabic adjectives, which are influenced by factors other than word length, the best predictor for the use of the superlative forms, and I found that SCE does show a preference for the periphrastic forms for disyllabic adjectives, especially those that have low frequencies and those that have high frequencies and alternate between the two forms in British English.